2012
DOI: 10.1016/j.neuro.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multi-well microelectrode arrays for neurotoxicity screening using a chemical training set

Abstract: Microelectrode array (MEA) approaches have been proposed as a tool for detecting functional changes in electrically excitable cells, including neurons, exposed to drugs, chemicals or particles. However, conventional single well-MEA systems lack the throughput necessary for screening large numbers of uncharacterized compounds. Recently, multi-well MEA (mwMEA) formats have become available to address the need for increased throughput. The current experiments examined the effects of a training set of 30 chemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
124
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 36 publications
16
124
0
1
Order By: Relevance
“…Higher concentrations of DomA (1 and 2 μM) also significantly decrease the MFR, whereas concentrations up to 0.1 μM of DomA do not cause any effect on MFR (Hogberg et al, 2011). In primary rat cortical neurons (12-22 DIV), DomA (50 μM) has been reported to reduce MFR by more than 90% (McConnell et al, 2012).…”
Section: Domoic Acid (Doma)mentioning
confidence: 88%
See 1 more Smart Citation
“…Higher concentrations of DomA (1 and 2 μM) also significantly decrease the MFR, whereas concentrations up to 0.1 μM of DomA do not cause any effect on MFR (Hogberg et al, 2011). In primary rat cortical neurons (12-22 DIV), DomA (50 μM) has been reported to reduce MFR by more than 90% (McConnell et al, 2012).…”
Section: Domoic Acid (Doma)mentioning
confidence: 88%
“…For example it has been shown that MEA-coupled neuronal cortical networks are very sensitive to pharmacological manipulation of the excitatory ionotropic glutamatergic transmission (Frega et al, 2012). MEAs can also be applied in higher throughput platforms to facilitate screening of numerous chemical compounds (McConnell et al, 2012). Excessive excitability can be also measured directly by evaluating the level of the extracellular glutamate using the enzyme-based microelectrode arrays.…”
Section: How It Is Measured or Detectedmentioning
confidence: 99%
“…As such, MEA recordings allow for reproducible screening of neurotoxic compounds with high sensitivity and specificity (McConnell et al, 2012;Valdivia et al, 2014;Nicolas et al, 2014). Despite the marked increase in mitochondrial activity, MEA recordings demonstrated that neuronal activity of primary cortical cultures is largely unaffected upon acute (30 min) exposure to TCP isomers, mixtures and CBDP (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, ToCP and TmCP may have different modes of action. So far, increases in MSR have been largely limited to glutamatergic agonists and GABAergic antagonists (McConnell et al, 2012;Mack et al, 2014). Since prolonged exposure to ToCP was recently reported to decrease glutamatergic signaling (Hausherr et al, 2014), it is tempting to speculate that the neurotoxicity of ToCP also involves modulation of glutamatergic receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation